THE ROLE OF MOTIVATION IN LEARNING FOREIGN LANGUAGE - Jo’raboyev Akmal, Jo’raboyev Akmal (Журнал иностранных языков и лингвистики, 2021)
this paper analyzes the role of motivation in language learning, especially foreign language acquisition. It compares two different subjects who are learning English yet they have various background of family, language learning experience, and interests. They were provided pre-, post-tests to testify their knowledge; moreover, they were interviewed to know how they are encouraged to learn a language. The paper indicates the importance of intrinsic motivation for second language learners.